Exploring self-presentation posts of people with depression: themes, stigma, and identity construction - Lei Gu; Xia Gao (Frontiers in Public Health)
IntroductionSocial media plays an increasingly influential role in shaping mental health communication. However, individual expressions related to self-presentation, particularly among people with depression, remain relatively understudied. This study aims to examine how individuals with depression construct and present their identities on Xiaohongshu (RED), a prominent Chinese social media platform.MethodsWe employed semantic network analysis and content analysis to investigate depression-related self-presentation narratives on Xiaohongshu. User posts were systematically analyzed to identify key themes and patterns in identity construction.ResultsThree primary themes driving self-presentation narratives were identified: Mental Health & Treatment, Life Stress & Emotion Management, and Self-awareness & Emotional Experience. These themes are intertwined with experiences of stigma and personal challenges, fostering a narrative shift toward optimism and resilience. This shift supports the formation of three distinct identity types: the Depressed Self, the Optimistic Self, and the Resilient Self. Cognitive biases such as negative filtering, overgeneralization, and catastrophizing were found to influence identity formation.DiscussionThe findings reveal the complex interplay between thematic narratives, cognitive biases, and stigma in online self-presentation among individuals with depression. The study highlights the pivotal role of social media in redefining mental health narratives and shaping online identity construction.